Putting the pieces together: 40 years of fertility trends across 19 post-socialist countries. Issue 5 (3rd September 2017) - Billingsley, Sunnee; Duntava, Aija
Abstract: Demographic change has been a key consequence of transition, but few studies trace fertility trends across countries over time. We describe fertility trends immediately before and after the fall of state socialism across 19 Central and Eastern European and Central Asian countries. We found a few common patterns that may reflect economic and political developments. The countries that experienced the most successful transitions and integration into the EU experienced marked postponement of parenthood and a moderate decline in second and third births. Little economic change in the poorest transition countries was accompanied by less dramatic changes in childbearing behavior. In western post-Soviet contexts, and somewhat in Bulgaria and Romania, women became more likely to only have one child but parenthood was not substantially postponed. This unique demographic pattern seems to reflect an unwavering commitment to parenthood but economic conditions and opportunities that did not support having more than one child. In addition, we identify countries that would provide fruitful case studies because they do not fit general patterns.